MENUMBUHKAN NILAI KEARIFAN LOKAL RELIGIUS PADA ANAK DENGAN METODE PEMBIASAAN BERBAHASA JAWA KRAMA MELALUI KARTU KATA DI RA MASYITHOH SANDEN - Siti Nur Uswatun Chasanah; bagus, Bagus Mahardika; Ahri Diah Istiqomah; Dita Yoani Amanda; Yeni Septiani (QURROTI, 2024)
Nowadays there are still many children who do not have language skills, especially Javanese. In their daily lives, children are more interested in using slang or mixed languages ​​for today's children as their daily language. A child's world is the initial foundation in forming character values, so that he or she can grow up intelligent, independent and have a superior personality. This research aims to find out about the habit of using Javanese language manners to foster local religious wisdom values ​​in children. The type of research used is qualitative research and uses a case study approach. Collecting and processing research data was carried out using observation, interviews and documentation techniques. The data analysis techniques include data collection, data reduction and drawing conclusions. From this research, the results obtained were that in an effort to foster local religious wisdom values ​​in children at RA Masyithoh Sanden, students were trained to get used to speaking Javanese manners. This habit starts from simple things, one of which is by playing vocabulary cards. The habit of using polite Javanese language not only fosters the value of local religious wisdom, but indirectly also instills the character of politeness. Because in Javanese there is a basic upload.